Expression of genes encoding interleukin 15 and its receptor subunits in the duodenal and colonic mucosae of dogs with chronic enteropathy - Rintaro Furukawa; Yuna Hara; Keiko Furuya; Kaho Takahashi; Rinka Nishimura; Tomoaki Shingaki; Hironari Osada; Hirotaka Kondo; Keitaro Ohmori (Veterinary and Animal Science, 2022)
A pro-inflammatory role of interleukin (IL)-15 and IL-15 receptor (R) in chronic intestinal inflammation, such as inflammatory bowel disease, has been reported in humans. However, the contribution of IL-15 signaling in the pathogenesis of canine chronic enteropathy (CE) remains unclear. Therefore, as a first step in elucidating the importance of IL-15 signaling in canine CE, we measured the mRNA expression of IL-15 and IL-15R subunits, including IL-15Rα, IL-15Rβ, and IL-15Rγ, in the duodenal and colonic mucosae of healthy dogs and those with CE, including food-responsive enteropathy (FRE), antibiotic-responsive enteropathy (ARE), and immunosuppressant-responsive enteropathy (IRE). Real-time PCR analysis revealed significantly lower IL-15Rα mRNA expression levels in the duodenal mucosa of dogs with IRE compared to healthy dogs. In contrast, the mRNA expression levels of IL-15, IL-15Rβ, and IL-15Rγ in the duodenal mucosa and IL-15, IL-15Rα, IL-15Rβ, and IL-15Rγ in the colonic mucosa did not differ among healthy dogs and those with FRE, ARE, or IRE. These findings suggest that decreased mRNA expression of IL-15Rα might be involved in the pathogenesis of duodenitis in dogs with IRE. Moreover, even in canine CE, IL-15 signaling appears to play different roles in duodenitis and colitis in dogs with FRE, ARE, and IRE. However, there were no correlations between the gene expression levels of IL-15Rα and clinical severity or histopathological scores in the duodenum of dogs with IRE. Further studies are necessary to investigate the IL-15Rα protein localization and to determine how impaired IL-15Rα expression contributes to the development of duodenitis in dogs with IRE.